A novel family of retrotransposon-like elements in Xenopus laevis with a transcript inducible by two growth factors. - Greene, J M (1993)
A cDNA clone named 1A11 was isolated in a screen for genes that are activated by both mesoderm inducing factors FGF and activin in animal explants of Xenopus laevis embryos. In undisturbed embryos, 1A11 is expressed during the gastrula stage in the entire marginal zone where mesoderm originates, and later in the somites, the tailbud, and at much lower levels in lateral mesoderm. The 1A11 sequence of 4.5 Kb has a 220 bp repeat at its ends, indicative of a retrotransposon-like structure. A long open reading frame encodes a predicted protein with only short homologies to the gag and protease regions of retroviruses and retrotransposons. Multiple copies of 1A11-related sequences were found in the Xenopus genome, constituting solo LTRs (long terminal repeats) of 1267 bp, and unique region copies (i.e., sequences internal to the repeats in the cDNA). Inverted repeats of 5 bp and apparent target site duplications of 5 bp surround the sequenced solo LTR. Thus, 1A11 is a new retrotransposon-like element in Xenopus laevis.